Evaluate the function, Algebra

Given f ( x ) = 2 + 3x - x2   and g ( x ) = 2 x -1 evaluate ( f + g ) ( 4)

Solution

Through evaluate we mean one of two things based on what is in the parenthesis. If there is a number in the parenthesis then we desire a number.  If there is an x (or no parenthesis, as that implies & x) then we will carry out the operation and simplify as much as possible.

( f + g ) ( 4)  = f ( 4) + g ( 4)

= (2 + 3( 4) - 42 ) + (2 + 4( -1)

= -2 + 7

= 5

Posted Date: 4/8/2013 1:16:26 AM | Location : United States







Related Discussions:- Evaluate the function, Assignment Help, Ask Question on Evaluate the function, Get Answer, Expert's Help, Evaluate the function Discussions

Write discussion on Evaluate the function
Your posts are moderated
Related Questions
Example: We are investing $100,000 in an account that earns interest at a rate of 7.5% for 54 months.  Find out how much money will be in the account if, (a) Interest is comp

Lisa and Judy read mystery novels. Judy has read three fewer than five times as many as Lisa. Equation: J=5L-3 Lisa: Judy:

how to find the multiplication factor


Pricing Problems Below give problem deal with some basic principles of pricing. Example A particular calculator has been marked up as 15% & is being sold for $78.50. How m


Sketch the graph parabolas. g ( x ) = 3x 2 - 6 x + 5 Solution For this parabola we've obtain a = 3 , b = -6 and c = 5 .  Ensure that you're cautious with signs while id

(x+a) (x+b) (x+c) =

what is a word problem for a nonlinear function?